Racial disparities in access to, and outcomes of, acute ischaemic stroke treatments in the USA - Mandip Dhamoon; David Daniel; Luke Kiefer; Sai Polineni (Stroke and Vascular Neurology)
Background Racism contributes to higher comorbid risk factors and barriers to preventive measures for black Americans. Advancements in systems of care, tissue plasminogen activator (tPA) availability and endovascular thrombectomy (ET) have impacted practice and outcomes while outpacing contemporary investigation into acute ischaemic stroke (AIS) care disparities. We examined whether recent data suggest ongoing disparity in AIS interventions and outcomes, and if hospital characteristics affect disparities.Methods We examined 2016–2019 fee-for-service Medicare inpatient data. We ran unadjusted logistic regression models to calculate ORs and 95% CI for two interventions (tPA and ET) and four outcomes (inpatient mortality, 30-day mortality, discharge home and outpatient visit within 30 days), with the main predictor black versus white race, additionally adjusting for demographics, hospital characteristics, stroke severity and comorbidities.Results 805 181 AIS admissions were analysed (12.4% black, 87.6% white). Compared with white patients, black patients had reduced odds of receiving tPA (OR 0.71, 95% CI 0.69 to 0.74, p<0.0001) and ET (0.69, 95% CI 0.65 to 0.72, p<0.0001). After tPA, black patients had reduced odds of 30-day mortality (0.77, 95% CI 0.72 to 0.82, p<0.0001), discharge home (0.72, 95% CI 0.68 to 0.77, p<0.0001) and outpatient visit within 30 days (0.89, 95% CI 0.84 to 0.95, p=0.0002). After ET, black patients had reduced odds of 30-day mortality (0.71, 95% CI 0.63 to 0.79, p<0.0001) and discharge home (0.75, 95% CI 0.64 to 0.88, p=0.0005). Adjusted models showed little difference in the magnitude, direction or significance of the main effects.Conclusions Black patients were less likely to receive AIS treatments, and if treated had lower likelihood of 30-day mortality, discharge home and outpatient visits. Despite advancements in practice and therapies, racial disparities remain in the modern era of AIS care and are consistent with inequalities previously identified over the last 20 years. The impact of hospital attributes on AIS care disparities warrants further investigation.